The Influence of Students Verbal Communication Skills on the Quality of Classroom Presentation in Biology Study Program Students Batch 2023 of Medan State University - Amanda, Dhea; Feriska, Jihan; Poluan, Nadia Amelia Elyana; Andini, Najwa; Purba, Vennia Marsella (CONTENT: Journal of Communication Studies, 2024)
This research aims to examine the influence of verbal communication skills on the presentation quality of students of the Stambuk Biology Study Program 2023 at Medan State University. Verbal communication skills are considered an important component in the context of higher education, especially in the presentation process in the classroom which is often used as the main method to measure students' understanding and analytical skills. This study used a quantitative descriptive method with the research population of all students of the Stambuk Biology Study Program 2023 which numbered 124 people, and the sample was taken as many as 95 respondents. Data is collected through observations and questionnaires on the Likert scale to measure the level of verbal communication skills and presentation quality. The results showed that there was a very strong positive correlation between verbal communication skills and the presentation quality of Biology students at Medan State University, with a Pearson Correlation score of 0.901. However, the majority of students have low verbal communication skills and presentation quality. This research emphasizes the importance of improving verbal communication skills to improve the quality of student presentations. Especially Biology students at Medan State University